RETRACTED: A Complex Diarrhea or an Intricate Diagnosis? A Case Report - Zaffina, Isabella; Grossi, Maria Maddalena; Settino, Chiara; Scarpelli, Serena; Picciarella, Alice; Muto, Pietro; Forte, Valentina; Florio, Letizia; Calderaro, Alessandra; Arone, Andrea; Provenzano, Pietro; D’Amico, Eugenio (Global Journal of Medical and Clinical Case Reports, 2025)
Diarrhea is not a solitary illness but is a part of different conditions. It is characterized by a rise in gut movements and an augmented liquidity of stools. Diarrhea can be acute or chronic concerning the duration of symptoms, and infectious or non-infectious concerning etiology. The differential diagnosis is noticeably large and consequently, the diagnostic tools and pathway are very multifaceted. We present the case of a 74-year-old male, with a history of acute abdominal pain, diarrhea, and fever. Several exams were made but only an examination of the stool samples came back positive for Anisakis. It is a risen infection due to augmented consumption of undercooked fish. Most cases are overlooked because of the wide-ranging variety of symptoms that make the diagnosis challenging. The diagnosis is based on the endoscopy or laparotomy. In symptomatic patients’ physical removal of the Anisakis larva using an endoscope is often curative, while anthelmintics, such as albendazole, can be used although they are not extremely efficacious. Though it is an unusual infection, clinicians should be conscious of it in patients with gastrointestinal symptoms.